Are the Keyboards Weightier than the Biros? The Effect of Computer-Based Testing on Students’ Achievement and Anxiety in Mathematics - ADENEYE OLAREWAJU AWOFALA (Universitas Sebelas Maret, 2020)
Are the keyboards weightier than the biros? This question is the focus of the present study in which the investigation of the modes of testing in mathematics (computer-based testing-CBT and paper-based testing-PBT) was carried out using mathematics achievement and mathematics anxiety as dependent measures. Through a pre-test post-test experimental research, the study tested two null hypotheses at 0.05 level of significance using an independent samples t-test. The study lasted for four weeks in two Nigerian senior secondary schools. Results showed that there was no statistically significant difference between the mean mathematics achievement scores of students tested by the computer-based test and the paper-based test. Also, there was no significant difference between the mean mathematics anxiety scores of students tested by the computer-based test and the paper-based test. The implication of these results is that assessing students using the two modes showed no variations in their achievement and anxiety in mathematics. Thus, the mode of testing showed no differential effect on students’ learning outcomes in mathematics. Based on the findings of this study, government at levels in Nigeria need to put in place the enabling environment and infrastructural facilities needed for schools to benefit fully from the advantages inherent in the CBT mode of assessment.